2020
DOI: 10.1097/sla.0000000000004486
|View full text |Cite
|
Sign up to set email alerts
|

Two-year Outcomes of Prehabilitation Among Obese Patients With Ventral Hernias

Abstract: Objective: To determine if preoperative nutritional counseling and exercise (prehabilitation) improve outcomes in obese patients seeking ventral hernia repair (VHR)? Summary Background Data: Obesity and poor fitness are associated with complications following VHR. It is unknown if preoperative prehabilitation improves outcomes of obese patients seeking VHR. Methods: This is the 2-year follow-up of a blinded randomized controlled trial from 2015 to 2017 at a safety-net academic institution. Obese patients (BMI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 31 publications
(66 reference statements)
0
34
0
Order By: Relevance
“…Many of the patients included in this trial were at high risk for recurrence given presence of co-morbidities and prior abdominal surgeries 2 . It is unclear if the recurrence rates will taper off and be similar to our other published trials at 24 to 36 months 16,17 . The 2-year and 3-year results will shed more light on the timing of recurrence and the overall rate.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Many of the patients included in this trial were at high risk for recurrence given presence of co-morbidities and prior abdominal surgeries 2 . It is unclear if the recurrence rates will taper off and be similar to our other published trials at 24 to 36 months 16,17 . The 2-year and 3-year results will shed more light on the timing of recurrence and the overall rate.…”
Section: Discussionmentioning
confidence: 56%
“…As this was not our primary outcome, we are unable to conclude if this is a true finding or secondary to chance. These results should be framed in conjunction with our prior RCTs with 2-year reoperation rates following LVHR of 1%–2% 16,17 . Given our results and assuming true effect size is 50% lower (4.5% vs 0.5% reoperation rate), 476 patients would be needed for an appropriately powered study to detect a true difference.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Most of these patients might not achieve the target weight to become optimal candidates for hernia repair, which prevents them from having a better quality of life and keeps them at risk for acute incarceration and strangulation 12. In one randomized clinical trial enrolling 118 obese patients with ventral hernias, only 12 patients (20%) were able to achieve the target weight loss of 7% of total body weight even with a prehabilitation program, and only half of them were able to maintain that weight loss after 2 years 8…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent report of the same study with 2 years of follow-up found no difference between the two groups in the percentage of hernia-free and complication-free patients (72.9 vs. 66.1%, p ¼ 0.424). 27 Further research is warranted before these findings can be generalized to the larger VHR population; it is possible that a personalized approach, as opposed to a one-size-fits-all program, provides longer lasting results. 28 Beyond these early conclusions, the many similarities between the abdominal wall and musculoskeletal tendons provide a solid physiopathological basis to support exercise conditioning before VHR.…”
Section: Physical Conditioningmentioning
confidence: 99%